2019
DOI: 10.1017/s0950268819001882
|View full text |Cite
|
Sign up to set email alerts
|

A tuberculosis school outbreak in China, 2018: reaching an often overlooked adolescent population

Abstract: Adolescents have been largely neglected from tuberculosis control efforts. In low- to medium burden settings much of the tuberculosis burden in this age group occurs from school outbreaks. We report on a large tuberculosis outbreak in adolescents from a boarding high school in Jiangsu Province, China. From March to June 2018, a tuberculosis outbreak occurred in a boarding high school. We conducted an outbreak investigation involving clinical diagnostic tests and molecular analysis to determine the outbreak ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
14
0
2
Order By: Relevance
“…Each MIRU locus was amplified individually with primers specific for sequences flanking the MIRU units ( Supplementary Table S1 ). In the current study, we used a set of 12 VNTR loci ( 20 , 21 ). The PCR reaction mixture for all loci was listed in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Each MIRU locus was amplified individually with primers specific for sequences flanking the MIRU units ( Supplementary Table S1 ). In the current study, we used a set of 12 VNTR loci ( 20 , 21 ). The PCR reaction mixture for all loci was listed in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Unsurprisingly, the risk of TB transmission among AYA in schools increases with increasing proximity and duration of exposure. Contact investigations that recorded classroom seating charts found that students who were routinely seated next to a student with TB had the highest incidence of TB infection [26,79,80]. School building designs that reduce shared air may conversely limit transmission, as with one outbreak that affected only a single classroom that opened directly to the outdoors and did not share a corridor with other classrooms [80].…”
Section: School Exposuresmentioning
confidence: 99%
“…School-based transmission from an adult teacher to an adolescent student with fewer than 10 h of contact has also been reported [83]. Delayed discovery of active TB cases and delayed contact investigations feature in many school outbreaks, leading to extensive spread of infection [26,[78][79][80][82][83][84][85].…”
Section: School Exposuresmentioning
confidence: 99%
“…Current measures to prevent and control of TB are often focused on adults, while adolescents are often neglected in China. In recent years, some school based TB outbreaks have been reported in China [2][3][4][5][6][7], which attracts considerable attention. Data from released annual report on surveillance of infectious disease in China in 2017, 835193 TB cases were notified in China, among which, 40656 (4.87%) were students, incidence of pulmonary TB was 15.47/100000 students, and incidence of smear positive of pulmonary TB was 2.64/100000 students, the proportion of laboratory confirmed TB ranged from 8.3% to 20.8% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Data from released annual report on surveillance of infectious disease in China in 2017, 835193 TB cases were notified in China, among which, 40656 (4.87%) were students, incidence of pulmonary TB was 15.47/100000 students, and incidence of smear positive of pulmonary TB was 2.64/100000 students, the proportion of laboratory confirmed TB ranged from 8.3% to 20.8% [8]. In China, high school students face serious challenge for college entrance examination, because of high pressure and overcrowded conditions, school based TB outbreaks usually occurred in boarding school system [2,7]. Diagnosis of tuberculosis in students often relies on symptoms screening, chest radiography and smear examination, and the low proportion of laboratory confirmed TB and few of positive strains isolated from TB students, which make transmission investigation more difficult.…”
Section: Introductionmentioning
confidence: 99%